Penerapan metode pembelajaran kooperatif tipe make a match dalam meningkatkan hasil belajar peserta didik - Istifaul Ikhlila; Adeng Hudaya; Fajar Kurniadi (Universitas Indraprasta PGRI, 2022)
the aim of this study was to determine the effect of applying the Make A Match cooperative learning method in improving the learning outcomes of class X students at SMA Budhi Warman 1, East Jakarta. The research method used is the experimental method with the design used is the true experimental design for the posttest only control design. The population of this study were all students of class X SMA Budhi Warman 1 East Jakarta and the samples were class X IPS 1 and X IPS 2. The instrument used was a multiple choice test with 13 validated questions. The research results obtained: There is an effect of applying the make a match type of cooperative learning method in improving the learning outcomes of class X students at SMA Budhi Warman 1 East Jakarta. This is shown by the t test, where the value t-count = 25.72 is greater than the value t-Table = 2.015 for α = 0.05.